A Testing Pattern for Automatic Control Software Addressing Different Degrees of Process Autonomy and Cooperation - Saglietti, Francesca; Lill, Raimar (Proceedings 19th IFAC World Congress, 2014)
This article considers different automatic control paradigms allowing for varying degrees of agent cooperation and autonomy. In order to support the automatic verification of safety-relevant software controllers, it proposes the use of a generic testing pattern which can be instantiated such as to allow to optimize automatic test data generation with respect to the specific targets of the application considered and of the testing phase involved. The article reports on successful case studies carried out in different real-world environments. <br
UnivIS-Import:2015-04-17:Pub.2014.tech.IMMD.lsinfs_1.atesti

Evolution of Verification Techniques by Increasing Autonomy of Cooperating Agents - Saglietti, Francesca; Söhnlein, Sven; Lill, Raimar (Autonomous Systems: Developments and Trends, 2011)
As system parts are becoming increasingly decoupled, gaining at the same time in terms of local autonomy, this article elaborates on the effects this trend has on verification and validation techniques. Both qualitative approaches to fault detection and quantitative approaches to reliability assessment are analyzed in the light of their evolution to adapt to the increasing decentralization and autonomy of modern 'systems of systems'.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.lsinfs_1.evolut

Model-Based Design and Testing of Decisional Autonomy and Cooperation in Cyber-Physical Systems - Saglietti, Francesca; Föhrweiser, David; Winzinger, Stefan; Lill, Raimar (Proceedings EUROMICRO SEAA 2015, 2015)
This article presents a study on the benefits offered by Coloured Petri Nets in capturing and separating permanent and temporary behavioural information and on the systematic support they hereby provide to model-based design and testing of cyber-physical systems. In particular, it illustrates the application of CPN modelling to capture the behaviour of cooperative mobile robots and highlights their benefits in terms of compactness and scalability. Finally, the article reports on the applicability of test case generation algorithms supporting the coverage of the underlying CPN models with respect to different testing criteri
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.lsinfs_1.modelb
Keywords: Autonomy; Coloured Petri Nets; Cooperation; Cyber-physical Systems; Model-based Design; Model-based Testing

Model-based Testing of Autonomous Systems based on Coloured Petri Nets - Lill, Raimar; Saglietti, Francesca (ARCS 2012 Workshops, 2012)
The use of autonomous systems, including cooperating agents, is indispensable in certain fields of application. Nevertheless, the verification of autonomous systems still represents a challenge due to lack of suitable modelling languages and verification techniques. To address these difficulties, different modelling languages allowing concurrency are compared. Coloured Petri Nets (CPNs) are further analysed and illustrated by means of an example modelling autonomous systems. Finally, some existing structural coverage concepts for Petri Nets are presented and extended by further criteria tailored to the characteristics of CPNs. © 2012 Gesellschaft fuer Informatk.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.lsinfs_1.modelb

Model-based Testing of Cooperating Robotic Systems using Coloured Petri Nets - Lill, Raimar; Saglietti, Francesca (SAFECOMP 2013 - Workshop DECS (ERCIM/EWICS Workshop on Dependable Embedded and Cyber-physical Systems) of the 32nd International Conference on Computer Safety, Reliability and Security, 2013)
This article proposes a model-based testing approach for cooperating robotic systems. Coloured Petri Nets are used for capturing the high behavioural multiplicity of such systems in a compact and scalable way. For the purpose of systematically extracting test cases from underlying models, a number of coverage criteria based on different model entities is introduced. Finally, in order to ensure practicality, an incremental testing procedure based on increasingly refined coverage concepts is proposed. <br
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.lsinfs_1.modelb

Model-based Testing of Cooperating Robotic Systems using Coloured Petri Nets - Lill, Raimar; Saglietti, Francesca (SAFECOMP 2013 - Workshop DECS (ERCIM/EWICS Workshop on Dependable Embedded and Cyber-physical Systems) of the 32nd International Conference on Computer Safety, Reliability and Security, 2013)
This article proposes a model-based testing approach for cooperating robotic systems. Coloured Petri Nets are used for capturing the high behavioural multiplicity of such systems in a compact and scalable way. For the purpose of systematically extracting test cases from underlying models, a number of coverage criteria based on different model entities is introduced. Finally, in order to ensure practicality, an incremental testing procedure based on increasingly refined coverage concepts is proposed. <br
UnivIS-Import:2015-04-20:Pub.2013.tech.IMMD.lsinfs_1.modelb_6
Keywords: Safety; Embedded systems; model-based testing; cooperating autonomous systems; Coloured Petri Nets; coverage metrics; incremental testing procedure

Reconfiguration Testing for Cooperative Autonomous Agents - Saglietti, Francesca; Winzinger, Stefan; Lill, Raimar (Computer Safety, Reliability, and Security, SAFECOMP 2015 Workshops, 2015)
In order to verify reconfiguration of interacting autonomous agents to be exclusively beneficial and never hazardous to cyber-physical systems, this article suggests a systematic approach based on incremental model-based testing and illustrates its application to cooperating mobile robot
UnivIS-Import:2015-07-08:Pub.2015.tech.IMMD.lsinfs_1.reconf_7
Keywords: Cyber-physical systems; robots; autonomous agents; cooperation; reconfiguration; CPN modelling; incremental testing

Test Coverage Criteria for Autonomous Mobile Systems based on Coloured Petri Nets - Lill, Raimar; Saglietti, Francesca (FORMS/FORMAT 2012, 2012)
For the purpose of testing the cooperative behavior of software-controlled autonomous systems, a model-based testing approach is presented. It makes use of Coloured Petri Nets providing a compact and scalable representation of behavioral multiplicity to be covered by an appropriate selection of representative test scenarios fulfilling net-based coverage criteria.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.lsinfs_1.testco_5
Keywords: Autonomous mobile systems; Coloured Petri Nets; Model-based testing; Test coverage criteria

Testing the Cooperation of Autonomous Robotic Agents - Lill, Raimar; Saglietti, Francesca (Proceedings of the 9th International Conference on Software Engineering and Applications - ICSOFT-EA, 2014)
This article proposes an approach to testing the cooperative behaviour of autonomous software-based agents with safety-relevant tasks. It includes the definition of different model-based testing criteria based on the coverage of Coloured Petri Net entities as well as the automatic generation of appropriate test cases. The multi-objective optimization problem considered addresses both the maximization of interaction coverage and the minimization of the amount of test cases required. The approach developed for its solution makes use of genetic algorithms. The resulting automatic test case generation process is presented in this article together with the experiences gained by applying it to cooperating autonomous forklifts.
UnivIS-Import:2015-04-17:Pub.2014.tech.IMMD.lsinfs_1.testin_5
Keywords: Autonomous systems; Coloured petri nets; Genetic algorithms; Optimized test case generation; Structural testing